REMOVAL OF COLOR AND POLYPHENOLS FROM SUGARCANE MOLASSES ETHANOL VINASSE BY HYDRODYNAMIC CAVITATION - CASTILLO BOCANEGRA, KEYLA E. (2024)
THE HYDRODYNAMIC CAVITATION PROCESS USING ORIFICE PLATES WAS APPLIED TO REMOVE COLOR AND POLYPHENOLS FROM SUGARCANE MOLASSES ETHANOL VINASSE, WITH A TREATMENT TIME OF 1 H. THE RAW VINASSE WAS DILUTED WITH TAP WATER IN A VOLUME RATIO OF 1:10 IN AN ACIDIC MEDIUM (PH 2). A 2K FACTORIAL ANALYSIS WAS CARRIED OUT TO EVALUATE THE EFFECT OF THE INLET PRESSURE OF 2 AND 3.6 BAR. THE RESULTS INDICATE THAT THE INTERACTION BETWEEN THE INLET PRESSURE AND THE NUMBER OF ORIFICES HAS A SIGNIFICANT EFFECT ON THE COLOR AND POLYPHENOL REMOVAL EFFICIENCY. THE PLATE WITH 9 ORIFICES UNDER THE CONDITION OF AN INLET PRESSURE OF 3.6 BAR WAS MORE EFFICIENT, ACHIEVING A MAXIMUM COLOR REMOVAL OF 32.71% AND POLYPHENOL REMOVAL OF 88.62% DURING A 20 MIN TREATMENT, WITH A CAVITATION YIELD OF 0.00365 MG J-1. THE REQUIREMENT OF A LONGER TREATMENT TIME DID NOT FAVOR THE REMOVAL EFFICIENCY OF COLOR AND POLYPHENOLS. HYDRODYNAMIC CAVITATION SIGNIFICANTLY IMPROVES THE REMOVAL OF COLOR AND POLYPHENOLS, BEING A VIABLE ALTERNATIVE TO REDUCE TOXICITY IN ALCOHOLIC VINASSE, CONTRIBUTING TO ENVIRONMENTAL IMPROVEMENTS FOR THE ALCOHOL INDUSTRY. COPYRIGHT © 2024, AIDIC SERVIZI S.R.L.